Moral Injury and Recovery in Uniformed Professionals: Lessons From Conversations Among International Students and Experts - Jin, Jonathan; Weiman, Kyle; Bremault-Phillips, Suzette; Vermetten, Eric (Frontiers in Psychiatry, 2022)
Introduction: In the course of service, military members, leaders and uniformed professionals are at risk of exposure to potentially morally injurious events (PMIEs). Serious mental health consequences including Moral Injury (MI) and PTSD can result. Guilt, shame, spiritual/existential conflict, and loss of trust are described as core symptoms of MI. These can overlap with anxiety, anger, reexperiencing, self-harm, and social problems commonly seen in PTSD. The experiences of General (retired) Romeo Dallaire and other international experts who have led in times of crisis can help us better understand MI and recovery. Objectives: In honour of Dallaire, online opportunities were created for international students and leaders/experts to discuss topics of MI, stigma, and moral codes in times of adversity as well as the moral impact of war. We aimed to (1) better understand MI and moral dilemmas, and (2) identify key insights that could inform prevention of and recovery from MI. Methods: Webinars and conversations of 75-90 minute duration on MI and recovery were facilitated by Leiden University, the University of Alberta and the Dallaire Institute for Children, Peace and Security between General Dallaire, world experts, and graduate students. Sessions were recorded, transcribed and thematically analyzed with NVivo using standard qualitative methodology. Results: 94 participants engaged in conversations. Student engagements were attended by participants (N=51; female (29), male (22)) from the Netherlands and Canada. Conversations were held with international experts (N=43; female (19) and male (24)) from North America, Europe, Australia and the global south. Themes included: (1) recognizing the impact of exposure to PMIEs, (2) reducing stigma around MI, and (3) embracing the spiritual depth of humanity. Discussion: Exposure to PMIEs can have devastating impacts on military members, leaders and other uniformed professionals. This may lead to development of MI and PTSD. Recognizing MI as honorable may reduce stigma and psychological harm, and facilitate help-seeking among uniformed personnel and other trauma-affected populations. Salient efforts to address MI must include use of accurate measurements of MI and integrated holistic therapeutic approaches, inclusive of spiritual and social components. Urgency remains regarding the prediction, identification and treatment of MI.